The Portrayal of Cleopatra in Samuel Daniel’s The Tragedie of Cleopatra and William Shakespeare’s Antony and Cleopatra: A New Historicist Perspective - Sweidan, Mo’ath; Al-Khawaldeh, Samira (Jordan Journal of Modern Languages & Literatures, 2023)
Cleopatra VII is a major contender for the title of Egypt’s most famous woman in antiquity. There is a plethora of interdisciplinary studies to fathom the depths of her character and influence. Since literature is an amalgamation of human experience, this paper delves into two literary masterpieces exploring the variations on the portrayal of Cleopatra in British drama. The plays under scrutiny are Samuel Daniel’s The Tragedie of Cleopatra (1594) and William Shakespeare’s Antony and Cleopatra (1606). The significance of this paper lies in bringing the plays together compare and contrast, within the theoretical framework of new historicism so as to examine them with reference to their original milieu. The question the study poses is how and why Cleopatra’s portrayal varies greatly from one decade to another and from one author to another; hypothesizing that the variations are due to the changes in certain institutions (the monarchy, for instance).